2019
DOI: 10.1016/j.jbior.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

IL-7R-mediated signaling in T-cell acute lymphoblastic leukemia: An update

Abstract: Interleukin 7 (IL-7) and its receptor (IL-7R, a heterodimer of IL-7Rα and γc) are essential for normal lymphoid development. In their absence, severe combined immunodeficiency occurs. By contrast, excessive IL-7/IL-7R-mediated signaling can drive lymphoid leukemia development, disease acceleration and resistance to chemotherapy. IL-7 and IL-7R activate three main pathways: STAT5, PI3K/Akt/mTOR and MEK/Erk, ultimately leading to the promotion of leukemia cell viability, cell cycle progression and growth. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 123 publications
0
44
1
Order By: Relevance
“…An anti-IL-7 receptor (IL-7Rα) antibody, B12, has also recently been described to induce potent NK cell-mediated ADCC against T-ALL (177). Studies previously showed that IL-7 is an important factor in the progression of T-ALL, enhancing cell expansion and survival (248), making it an attractive target for antibody therapy. In addition to stimulating NK cell ADCC, B12 appears to be rapidly internalized and trafficked into lysosomes of leukemic cells, demonstrating its additional therapeutic potential, such as for intracellular drug delivery.…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
“…An anti-IL-7 receptor (IL-7Rα) antibody, B12, has also recently been described to induce potent NK cell-mediated ADCC against T-ALL (177). Studies previously showed that IL-7 is an important factor in the progression of T-ALL, enhancing cell expansion and survival (248), making it an attractive target for antibody therapy. In addition to stimulating NK cell ADCC, B12 appears to be rapidly internalized and trafficked into lysosomes of leukemic cells, demonstrating its additional therapeutic potential, such as for intracellular drug delivery.…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
“…5a, far left panel). Not surprisingly, given the high frequency of Notch activating mutations [3,26] and the role of IL-7 in T-ALL, this profile was associated with increased Notch activation and increased availability to respond to IL-7, as indicated by higher average expression of Notch1 and its targets Hes1 and IL-7r, respectively (Fig. 5a, left, right, and far right panels).…”
Section: Gene Expression Profiling Reveals a Notch/il-7/ Skp2 Signatumentioning
confidence: 95%
“…2c and S2B), suggesting Notch-independent Skp2 regulation. As the culture conditions included IL-7, a cytokine required for T-cells survival and proliferation and involved in p27 Kip1 regulation [24][25][26], we measured the distinct contribution of IL-7 and Notch activation to Skp2 expression. Skp2 expression and thymocyte mitogenic activity were sustained above basal level by IL-7 alone and were significantly upregulated in the presence of Notch signaling ( Fig.…”
Section: Skp2 Expression In Thymocytes Is Upregulated By Notch Signalmentioning
confidence: 99%
“…The deregulation of IL7/IL7R signaling can promote cancer development [129]. In particular, this deregulation is associated with leukemogenesis, e.g., acute lymphoblastic leukemia (ALL) of T-and B-cell origin development [130,131] and chronic lymphocytic leukemia [132]. To target lymphoblastic cancer cells, DAB389IL7, was constructed.…”
Section: Targeting Interleukin-7 Receptor (Il-7r)mentioning
confidence: 99%